Business hack the wealth dragon way to build a successful business in the digital age - Lee, John 1981- (Gildan, 2019)
Business Hack is your essential roadmap to business growth and online marketing success. Author and successful entrepreneur John Lee shares his proven methods to harness the power of online tools, including using social media--offering practical steps to create and implement highly effective cyber-marketing campaigns.
Online resource; title from title details screen (OverDrive, viewed April 5, 2019)
Keywords: Internet marketing; Selling; Success in business; Marketing sur Internet; Vente; Succès dans les affaires; selling; BUSINESS & ECONOMICS; Entrepreneurship; Downloadable audio books; Audiobooks; Livres audio